Efectos de la recaudación de impuestos en la ejecución presupuestal de la Municipalidad Provincial de San Martín. Periodo 2008 - 2012 - Cabrera Villalobos, Yhudith (2014)
The purpose of this research is. "Explain the effects of tax collection in the budget execution of the Provincial Municipality of San Martin. Period 2008 - 2012 " The generic question seeks to explain what were those effects for which it has raised the following hypothesis. "The effects of tax collection during the period 2008 - 2012 have been positive in the budget execution of the provincial municipality of San Martín". The methodology of the selection of a population of 30 people linked to the management of both variables in the municipality. The population is also assumed to be small as shown. This type of research is applied in the Explanatory level and design of ít is not Experimental Explanatory Transactional type, by using the analytical method – synthetic and deductive - inductive ASIGO of techniques and instruments have allowed the testing of hypothesis, ie by the survey and document analysis. From the results, analysis, interpretation and discussion, which in turn has allowed the hypothesis whereby it is determined that the effects of tax collection in the budget execution have been positive for the city and was carried out in this regard and in relation to specific objectives, conclusions and recommendations for the study period are formulated.